Effect of spironolactone with angiotensin receptor blocker on albuminuria in type 2 diabetic patients with nephropathy - Mahmud, Hasan; Hai, A. N. M. Abdul; Ahammod, Tofael (International Journal of Advances in Medicine, 2022)
Background: Diabetic nephropathy is the most important cause of the end-stage renal disease (ESRD). The aim of the study is to evaluate the effect of spironolactone 25 mg once daily in addition to losartan 50 mg once daily for 12 weeks for proteinuria reduction in diabetic nephropathy. Methods: This is a prospective clinical trial was carried out in the department of nephrology, national institute of kidney diseases and urology (NIKDU), Dhaka, Bangladesh from March 2015 to April 2016. A total of 60 patients attended the study considering inclusion and exclusion criteria. Proper ethical consent was taken from the relevant. Collected data were classified, edited, and analyzed into the computer for statistical analysis using SPSS version 22. Results: The mean serum creatinine baseline, end of 1st, 4th, 8th, and 12th weeks were significantly low (p<0.05) in the control group and significantly decline (p<0.05) in subsequent follow-up in both Intervention and control groups. The mean serum potassium- baseline, end of 1st, 4th, 8th, and 12weeks were not statistically significant (p>0.05) and significantly increased (p<0.05) in both groups. Improvement of urine albumin creatinine ratio was found 96.7% and 83.3% at end of 12th weeks in both groups respectively. It was observed that mean eGFR-baseline, end of 4th and 12th weeks were statistically significantly higher (p<0.05) in both groups with baseline. Conclusions: The addition of spironolactone 25 mg once daily with losartan potassium 50 mg daily for a 12-week period did not show a significant role in the reduction of proteinuria in diabetic nephropathy patients.